Coordenação Intragovernamental para a Implementação da Política Externa Brasileira: O Caso do Fórum IBAS - Carlos Aurélio Pimenta de Faria; Joana Laura Marinho Nogueira; Dawisson Belém Lopes (Universidade do Estado do Rio de Janeiro, 2012)
This study evaluates the organizational mechanisms and structures adopted by the Brazilian Ministry of Foreign Affairs (Itamaraty) to promote the coordination of domestic government actors for implementing the guidelines of the IBSA Forum (India, Brazil, and South Africa), created in 2003. After reviewing some of the factors that have led Itamaraty to lose its traditional insulation, the authors classify the mechanisms for intra-governmental coordination and analyze its dynamics, focusing special attention on the 16 thematic working groups created to ensure the achievement of IBSA's objectives. In the final remarks, the authors question Itamaraty's purported loss of capacity for intra-governmental coordination.